Basic Competency Level Of Vocational Teachers In Understanding The Curriculum 2013 - Wachidi Wachidi; Harun Joko Prayitno; Syamsul Hidayat; Muh. Nur Rochim Maksum (Unib Press, 2022)
The general purpose of this research is to determine the basic level of Competence of vocational teachers in understanding the Curriculum in 2013 in Bengkulu City. The specific purpose of this research is: (1) To find out the level of professional Competence of vocational teachers in understanding the Curriculum in 2013 in Bengkulu City; (b) To find out the level of pedagogic Competence of vocational teachers in understanding the Curriculum in 2013 in Bengkulu City; (c) To find out the level of personality competence of vocational teachers in understanding the Curriculum in 2013 in Bengkulu City; (d) To find out the level of social Competence of vocational teachers in understanding the 2013 curriculum in Bengkulu City. This research method uses a descriptive-analytical research approach. This research wants to describe the basic competency level of vocational teachers in understanding the Curriculum in 2013. This research place is at SMK in Bengkulu City. The population in this research were all vocational teachers in Bengkulu City. This research sample relates to the level of Competence of vocational teachers in understanding the Curriculum in 2013, amounting to 50 teachers. Sampling is used using random sampling techniques with lottery techniques—data collection techniques using questionnaires and documents. Questionnaires are used to trace data on the basic level of Competence of vocational teachers in understanding the Curriculum in 2013. To see and prove that the questionnaire is valid is done expert validation. The document was used to collect data on the number of teachers in SMK Kota Bengkulu. After the data is verified, processed with statistical percentage techniques, analyzed, and made conclusions. The study concluded that: (1) The level of pedagogical Competence of teachers of SMK Kota Bengkulu in understanding the Curriculum in 2013 amounted to 52% (Very UnderstandingUnderstanding) and 48% (Sufficient Understanding); (2) The level of professional Competence of teachers of SMK Kota Bengkulu in understanding the Curriculum in 2013 amounted to 31.5% (Sufficient Understanding) and 68.5 % (Very UnderstandingUnderstanding); (3) The level of personality competence of teachers of SMK Kota Bengkulu in understanding the Curriculum in 2013 amounted to 17.3% (Sufficient Understanding) and 82.6 % (Very UnderstandingUnderstanding); (4) The level of social Competence of teachers of SMK Kota Bengkulu in understanding the Curriculum in 2013 amounted to 42.4% (Sufficient Understanding) and 56.6% (Very UnderstandingUnderstanding).